Lead storage battery separator using glass fibers and heat-fusible organic fibers

By using AGM spacers composed of microglass fibers and hot-fusion organic fibers, and using ultrasonic sealing and other methods for bag processing, the problem of easy peeling of existing AGM spacers in cycle life tests is solved, high-strength and high electrolyte holding functions are achieved, and the life of lead-acid batteries is extended.

CN119631236APending Publication Date: 2025-03-14ENTEK ASIA INC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202380055897.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-25
Filing Date
2023-07-24
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the cycle life test of the existing AGM spacer, the bag processing part is easily peeled off, resulting in a decrease in the life of the lead-acid battery. At the same time, in the process of increasing the bonding strength of the spacer, the liquid absorbability of the electrolyte becomes worse, affecting the performance of the battery.

Method used

The AGM spacer consisting of microglass fibers and hot-fusion organic fibers is used, and bag processing is carried out by ultrasonic sealing and other methods to ensure that the peel strength of the sealing portion reaches 1N/20mm or more. At the same time, the fiber mixing ratio and resin selection are optimized to improve the puncture and tensile strength of the spacer.

Benefits of technology

The AGM spacer is achieved without peeling off the bag processing part during the cycle life test, which extends the life of the lead-acid battery, and improves the strength of the spacer and the electrolyte retaining function, meeting the high strength and electrolyte retaining function requirements of the spacer for lead-acid battery in recent years.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005255094050000191
    Figure BDA0005255094050000191
  • Figure BDA0005255094050000201
    Figure BDA0005255094050000201
Patent Text Reader

Abstract

Provided is a lead storage battery separator (AGM separator) which has high strength and a high electrolyte holding function required by a lead storage battery separator in recent years, and which does not cause peeling of a bag processing part (sealing part) during a cycle life test. The present invention relates to a separator for a lead storage battery, which is mainly composed of microglass fibers and heat-fusible organic fibers, and wherein the peel strength at a sealed part (fused part) of the separator is 1 N / 20 mm or more when the separator is boiled in water for 60 minutes after processing a bag sealed by ultrasonic waves.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an improvement of a separator used in a lead-acid battery, and more particularly to a solution to problems associated with battery manufacturing using an AGM (Absorbent Glass Mat) separator containing micro glass fibers and heat-fusible organic fibers. Background Art

[0002] In the past, liquid lead-acid batteries were used in automobile batteries. However, with respect to automobile lead-acid batteries in recent years, due to the popularization of the idling stop and start system (hereinafter referred to as ISS), the battery is no longer used only to use electricity when the engine is started as in the past. In addition to starting the engine, power is also supplied to the electrical system when the engine is stopped, and the charge and discharge cycle is performed more frequently than before.

[0003] At the same time, since the lead-acid battery is not in a fully charged state, the electrolyte is not stirred, resulting in a difference in specific gravity of the electrolyte (the stratification phenomenon of the electrolyte, hereinafter referred to as stratification) in the lead-acid battery, which becomes the main reason for reducing the battery life.

[0004] Therefore, instead of the conventional liquid lead-acid batteries, sealed lead-acid batteries having a life performance superior to that of liquid lead-acid batteries have also been used and are beginning to spread.

[0005] In the past, as a spacer for lead-acid batteries, a non-woven fabric made of micro glass fibers was used in order to have an electrolyte retention function. As for the spacer for lead-acid batteries composed of such a micro glass fiber non-woven fabric, it is usually used in a manner of being bent into a U-shape and wrapping any positive or negative plate. Therefore, since the two side ends of the spacer are in an open state, there is a possibility of a short circuit through the open part of the spacer. In addition, as for the plates used in lead-acid batteries, the mainstream is the cast plate (a plate using a cast grid), but recently, cheap expanded plates (a plate using an expanded grid) are also used. In the case of using an expanded plate, since the plate grid is easily deformed without the frame at the two side ends, the shedding of the active material becomes a problem, so in order to prevent a short circuit through the spacer, the spacer is bagged for use.

[0006] In the separator for lead-acid battery composed of micro-glass fiber non-woven fabric, in order to process the non-woven fabric into a bag, it is sufficient to join the non-woven fabric sheets on both sides of the U-shaped edges. However, originally, in order to make it have the function of retaining electrolyte, for non-woven fabric composed only of micro-glass fibers with fine fiber diameter and good electrolyte affinity, the non-woven fabric sheets cannot be joined. In the past, as a general joining method, a method of sealing the relative non-woven fabric sheets by heat sealing, ultrasonic sealing, gear sealing, etc. was proposed.

[0007] As a joining method using heat sealing or ultrasonic sealing, for example, as described in Patent Documents 1 to 4, a micro-glass fiber nonwoven fabric contains about 20 to 60% by weight of an organic material (polyethylene fiber, etc.) for imparting fusibility, instead of a glass fiber material (inorganic material) that does not inherently have fusibility.

[0008] In addition, as a joining method using gear sealing, for example, as described in Patent Documents 5 to 8, in a micro-glass fiber non-woven fabric, since it has no softness and elasticity and is brittle, instead of the glass fiber material that is easily damaged by pressure, impact, breakage, and cracking, an organic material (polyethylene terephthalate fiber, etc.) of about 30 to 50 weight % is contained to resist the high pressure and impact caused by gear biting and to prevent the non-woven fabric from breaking.

[0009] However, in the sealing methods by heat sealing, ultrasonic sealing, gear sealing, etc. of these patent documents 1 to 8, in order to enable the non-woven fabric to have an electrolyte retention function, the non-woven fabric composed only of micro-glass fibers with a fine fiber diameter and good electrolyte affinity contains about 20 to 60 weight % of organic materials (organic fibers) with low electrolyte affinity and coarse fiber diameter. Therefore, there is a problem of impairing the electrolyte retention function compared to the original non-woven fabric composed only of micro-glass fibers.

[0010] In addition, Patent Document 9 describes a sealable spacer comprising 10 to 25% heat-fusible core-sheath fibers and 0 to 5% monofilament heat-fusible fibers, with the total value of organic materials being 20 to 30%, and a spacer that is easily bonded using a gear seal and does not break at the bonding portion.

[0011] However, since the mixing ratio of the heat-fusible organic fiber is high in order to improve the bonding strength of the separator, the liquid absorption of the electrolyte is deteriorated by about 16 to 28% compared with the conventional example.

[0012] On the other hand, in a separator after bagging by ultrasonic sealing, peeling of the bagging portion (sealing portion) may occur during a cycle life test, which may cause a problem.

[0013] In the separator for lead-acid batteries after the cycle life test, peeling occurs in the bag processing part (sealing part) of the separator after bag processing using ultrasonic sealing. In the case of long-term use of the lead-acid battery, peeling also occurs in the bag processing part (sealing part) of the separator, which becomes a problem that reduces the life of the lead-acid battery.

[0014] This is believed to be because: in the cycle life test, the test was carried out in an overcharged state, so the electrolyte became hot, the bag processing part (sealing part) sealed by ultrasonic wave swelled in the electrolyte, the adhesion between the fibers was easily removed, and the sealing strength (peel strength) was reduced.

[0015] In addition, cost competition for lead-acid batteries for automobiles has become fierce, and improvement of production rhythm in battery manufacturing is indispensable. Therefore, high-strength AGM separators are required. Patent document 10 describes that in a non-woven fabric composed of 4 to 12% of heat-fusible binder fibers and glass fibers with an average fiber diameter of 3 μm or less, the bonding between fibers of the sheet is improved and the fluctuation of electrolyte permeability is suppressed.

[0016] As for the spacer shown therein, the thickness when pressurized at 20 kPa is 1.8 mm, which is relatively thick. Due to the thick thickness, even if the proportion of the hot-melt adhesive fiber as a reinforcing material is less than 12%, the absolute strength of the spacer itself is high, and it has a strength that does not affect the assembly workability of the lead-acid battery.

[0017] On the other hand, for the lead-acid batteries used in ISS in recent years, high-rate discharge characteristics are emphasized as one of the required performances of automotive batteries. In order to improve the high-rate discharge characteristics, the lead-acid battery plate spacing is designed to be narrow. Therefore, the thickness of the lead-acid battery separator is as thin as 1.8 mm, and therefore the absolute strength of the AGM separator is also reduced.

[0018] At the same time, in order to improve the assemblability of the lead-acid battery, an AGM separator having a high tensile strength (sheet strength) is required.

[0019] However, increasing the mixing ratio of organic fibers, which have a smaller specific surface area than fine glass fibers and have low hydrophilicity, tends to impair electrical resistance and liquid retention, which are basic characteristics of AGM separators.

[0020] Therefore, as a measure to improve the tensile strength (sheet strength) without increasing the mixing ratio of organic fibers as much as possible, it is considered to reduce the fineness of the heat-fusible organic fibers (make them thinner) or increase the number of fibers. However, if the fineness of the heat-fusible organic fibers is reduced, the organic fibers and glass fibers cannot be uniformly mixed due to the difference in specific gravity when the AGM spacer is manufactured, and the fluctuation of the characteristics of the AGM spacer becomes large, resulting in a problem that a stable quality AGM spacer cannot be obtained.

[0021] Similarly, recent lead-acid batteries need to be highly compressed to achieve higher capacity and longer battery life, and holes are easily formed due to the frame of the expanded plate, so the puncture strength of the AGM separator is required to be 6 N / mm or more.

[0022] Prior art literature

[0023] Patent Literature

[0024] Patent Document 1: Japanese Patent Application Laid-Open No. 57-098975

[0025] Patent Document 2: Japanese Patent Application Laid-Open No. 06-176749

[0026] Patent Document 3: Japanese Patent Application Laid-Open No. 09-017406

[0027] Patent Document 4: Japanese Patent Application Publication No. 2003-100276

[0028] Patent Document 5: Japanese Utility Model Application Publication No. 02-141955 (Japanese Utility Model Application Publication No. 02-034644 Microfilm)

[0029] Patent Document 6: Japanese Patent Application Publication No. 2004-127578

[0030] Patent Document 7: Japanese Patent Application Publication No. 2005-108617

[0031] Patent Document 8: Japanese Patent Application Publication No. 2003-297328

[0032] Patent Document 9: Japanese Patent Application Publication No. 2009-245901

[0033] Patent Document 10: Japanese Patent No. 6518094 Summary of the invention

[0034] Problems to be solved by the invention

[0035] The present invention has been made in consideration of such actual conditions, and an object of the present invention is to provide a separator for a lead-acid battery (AGM separator) which has high strength and high electrolyte retention function required for separators for lead-acid batteries in recent years and does not cause peeling of the bag processing part (seal part) during a cycle life test.

[0036] Means for solving problems

[0037] As a result of intensive studies to solve the above-mentioned problems, the separator for a lead-acid battery (AGM separator) of the present invention is a separator for a lead-acid battery having the following characteristics.

[0038] (1) A separator for a lead-acid battery, which is mainly composed of micro glass fibers and heat-fusible organic fibers, wherein the peel strength at the sealed portion (fusion portion) of the separator after bagging is 1 N / 20 mm or more when the separator is boiled in water for 60 minutes.

[0039] (2) The lead acid battery separator according to (1) above, wherein the bagging is performed by ultrasonic sealing.

[0040] (3) The separator for a lead-acid battery according to any one of (1) to (2), wherein the separator has a thickness of more than 0.50 mm and less than 1.80 mm when pressurized to 20 kPa.

[0041] (4) The separator for a lead-acid battery according to any one of (1) to (3) above, wherein the puncture strength of the separator is 6 N / mm or more.

[0042] (5) The separator for a lead-acid battery according to any one of (1) to (4) above, wherein the separator has a wettability of 100 sec / 3 ml or less.

[0043] (6) The separator for a lead acid battery according to any one of (1) to (5) above, wherein the separator has a tensile strength of 0.2 N / mm 2 above.

[0044] (7) The lead-acid battery separator according to any one of (1) to (6), wherein the heat-fusible organic fiber is an organic fiber having a core-sheath structure, and the sheath portion is a crystalline heat-fusible polyolefin resin or a crystalline heat-fusible polyester resin.

[0045] (8) The lead-acid battery separator according to any one of (1) to (6), wherein the heat-fusible organic fiber is an organic fiber having a core-sheath structure, and the sheath portion is an amorphous heat-fusible polyester resin.

[0046] (9) The separator for lead-acid batteries according to (8) above is characterized in that, in thermal analysis of the separator for lead-acid batteries using a differential scanning calorimeter (DSC), the glass transition temperature of the organic fiber derived from the core-sheath structure having the above-mentioned amorphous heat-fusible polyester resin is observed at 40°C to 100°C.

[0047] (10) The lead-acid battery separator according to any one of (1) to (9), wherein the heat-fusible organic fiber has a fineness of 0.4 dtex or more and 2.5 dtex or less.

[0048] (11) The separator for a lead-acid battery according to any one of (1) to (10) above, wherein the amount of the thermally fusible organic fiber blended is 10% by weight or more.

[0049] (12) The lead-acid battery separator according to any one of (1) to (11) above, wherein the number average fiber diameter of the microglass fibers is 4.5 μm or less.

[0050] (13) The lead-acid battery separator according to any one of (1) to (12) above, wherein the total amount of the microglass fibers and the thermally fusible organic fibers blended is 60% by weight or more.

[0051] (14) A lead acid battery using the separator for a lead acid battery according to any one of (1) to (13) above.

[0052] Effects of the Invention

[0053] The present invention can provide a lead-acid battery separator (AGM separator) which has high strength and high electrolyte retention function required for lead-acid battery separators in recent years and does not cause peeling of the bag processing part (seal part) during the cycle life test.

[0054] The bagging of the lead-acid battery separator (AGM separator) can be performed by heat sealing, ultrasonic sealing, gear sealing, etc., but the lead-acid battery separator (AGM separator) of the present invention does not peel off the bagging portion (sealing portion) when the bagging is performed by any method. In the present invention, when the bagging is performed by ultrasonic sealing, the effect of not peeling off the bagging portion (sealing portion) is higher. DETAILED DESCRIPTION

[0055] The separator for lead-acid batteries (AGM separator) of the present invention is wet-made mainly with microglass fibers and heat-fusible organic fibers, and in addition to the above-mentioned microglass fibers and the above-mentioned heat-fusible organic fibers, it may contain inorganic powders such as silica with excellent acid resistance and oxidation resistance, cellulose, carbon fibers, non-heat-fusible organic fibers or resins such as polyacrylonitrile fibers.

[0056] By adding non-thermally fusible monofilament polyester terephthalate fibers as the third component in addition to the above-mentioned thermally fusible organic fibers, a good quality AGM spacer without compression fracture (shearing) of the sealed portion can be obtained even when bag processing using gear sealing, heat sealing, ultrasonic sealing, etc. is performed.

[0057] By adding a monofilament-like organic fiber that does not have thermal fusibility, the compressive breaking strength (shearing force) of the nonwoven fabric can be increased (see, for example, Japanese Patent No. 4261821), and a better AGM separator can be obtained.

[0058] Furthermore, a complication effect can be expected by various combinations with materials that do not have thermal fusion properties.

[0059] The microglass fibers used in the lead-acid battery separator (AGM separator) of the present invention are preferably acid-resistant C glass fibers because they are used in an electrolyte (aqueous sulfuric acid solution with a specific gravity of 1.3). However, the microglass fibers are not limited to these as long as they are acid-resistant.

[0060] The fiber diameter of the microglass fiber also varies depending on the heat-fusible organic fiber and other auxiliary materials combined. One of the expected functions of the AGM separator is to suppress stratification. From this point of view, the number average fiber diameter is preferably 4.5 μm or less. In addition, when it is necessary to further improve the suppression of stratification in use in lead-acid batteries for ISS, the number average fiber diameter is more preferably 3.5 μm or less.

[0061] In the separator for lead acid battery (AGM separator) of the present invention, the amount of the micro glass fiber blended is preferably 60% by weight or more in order to maintain the absolute strength and electrolyte retention function of the AGM separator.

[0062] On the other hand, in order to maintain the tensile strength (sheet strength), puncture strength, and adhesion (peel strength) between AGM spacers of the AGM spacer, at least 10 wt% of heat-fusible organic fibers must be contained, and the blending amount of the microglass fibers is preferably 90 wt% or less.

[0063] The synthetic resin component of the above-mentioned heat-fusible organic fiber used in the separator for lead-acid batteries (AGM separator) of the present invention is a synthetic resin such as a polyethylene resin, a polypropylene resin, etc. polyolefin resin, polystyrene resin, polymethyl methacrylate resin, polyacrylonitrile resin, nylon resin, polyester resin, polyvinyl fluoride resin, etc., among which the heat-melting component is a polyethylene resin, a polypropylene resin, etc. polyolefin resin, and a heat-fusible polyester resin.

[0064] In the present invention, from the viewpoint of the effect of improving the tensile strength (sheet strength), it is preferable to use polyolefin resins such as polyethylene resins and polypropylene resins, polyester resins, and the like.

[0065] As the above-mentioned heat-fusible organic fiber, in order to improve the tensile strength (sheet strength), that is, to increase the number of heat-fusible organic fibers contained in the AGM spacer, heat-fusible organic fibers with a fineness of 2.5 dtex or less are preferred, heat-fusible organic fibers with a fineness of 1.6 dtex or less are more preferred, and heat-fusible organic fibers with a fineness of 1.5 dtex or less are further preferred.

[0066] When two or more types of heat-bonding organic fibers are mixed and used, the number average fineness of the heat-bonding organic fibers contained in the AGM separator is preferably 2.5 dtex or less, more preferably 1.6 dtex or less, and even more preferably 1.5 dtex or less.

[0067] If the fineness of the heat-fusible organic fiber is less than 0.4 dtex, the heat-fusible organic fiber and the microglass fiber are not uniformly mixed due to the difference in specific gravity when the AGM spacer is manufactured, and the fluctuation of the characteristics of the AGM spacer becomes large, and a problem of not being able to obtain an AGM spacer of stable quality occurs. Therefore, the fineness of the heat-fusible organic fiber is preferably 0.4 dtex or more, more preferably 0.5 dtex or more, and even more preferably 0.6 dtex or more.

[0068] The heat-bonding organic fiber used in the lead-acid battery separator (AGM separator) of the present invention preferably has a core-sheath structure.

[0069] In this case, the core may be a commonly used resin such as a polyolefin resin such as a polyethylene resin or a polypropylene resin, or a polyester resin, and preferably a resin having acid resistance, and more preferably a polyester resin.

[0070] The sheath part is preferably made of a polyolefin resin such as polyethylene resin or polypropylene resin, a polyester resin, or the like, and more preferably a crystalline polyolefin resin or a crystalline or amorphous polyester resin.

[0071] In the present invention, it is preferred to use a mixture of two or more types of thermally fusible organic fibers, and it is more preferred to use a mixture of two or more types of thermally fusible organic fibers having a core-sheath structure.

[0072] In the present invention, for at least one of the two or more mixed heat-fusible organic fibers having a core-sheath structure, when the sheath portion is composed of amorphous heat-fusible organic fibers (for example, amorphous Co-PET) having a glass transition temperature at 40°C to 100°C, the adhesion between the organic fibers during drying in the production process of the AGM spacer is improved, resulting in an AGM spacer with excellent tensile strength and puncture strength, and therefore it is preferred.

[0073] In the separator for lead-acid batteries (AGM separator) of the present invention, the blending amount (total amount) of the above-mentioned heat-fusible organic fibers is preferably 10 wt % or more, more preferably 15 wt % or more, and further preferably 20 wt % or more in order to maintain the tensile strength (sheet strength) and puncture strength of the AGM separator, and the adhesion (peel strength) between AGM separators.

[0074] If the content is less than 10% by weight, the tensile strength (sheet strength) and puncture strength of the AGM separator will be insufficient.

[0075] The blending amount (total amount) of the thermally fusible organic fibers is preferably 40% by weight or less, more preferably 35% by weight or less, and even more preferably 30% by weight or less.

[0076] When the content exceeds 40%, the ability of the AGM separator to retain the electrolyte decreases, and sulfuric acid released from the electrode plates during charging cannot be fully retained, causing stratification of the electrolyte.

[0077] In the present invention, when a heat-fusible organic fiber having a core-sheath structure in which the sheath is composed of a crystalline polyolefin resin and the core is composed of a polyester resin (e.g., PET / crystalline PE) is used alone as the above-mentioned heat-fusible organic fiber, the blending amount is preferably 15% by weight or more and 40% by weight or less, more preferably 20% by weight or more and 40% by weight or less, and further preferably 25% by weight or more and 40% by weight or less.

[0078] In addition, as the above-mentioned thermally fusible organic fiber, when two types of thermally fusible organic fibers having a core-sheath structure are used, it is preferred that the blending amount of the thermally fusible organic fiber having a core-sheath structure in which the sheath portion is composed of a crystalline polyolefin resin and the core portion is composed of a polyester resin (for example, PET / crystalline PE) is 10% by weight or more and 40% by weight or less, and the blending amount of the thermally fusible organic fiber having a core-sheath structure in which the sheath portion is composed of a crystalline polyester resin and the core portion is composed of a crystalline polyester resin (for example, PET / crystalline Co-PET) or the thermally fusible organic fiber having a core-sheath structure in which the sheath portion is composed of an amorphous polyester resin and the core portion is composed of a crystalline polyester resin (for example, PET / amorphous Co-PET) is greater than 0% by weight and less than 30% by weight, more preferably 5% by weight or more and less than 30% by weight, and further preferably 10% by weight or more and less than 30% by weight.

[0079] In the lead acid battery separator (AGM separator) of the present invention, the total content of the microglass fibers and the heat-fusible organic fibers is preferably 60 wt % or more, more preferably 65 wt % or more, and even more preferably 70 wt % or more.

[0080] In the separator for lead acid battery (AGM separator) of the present invention, the thickness of the AGM separator is preferably a thickness exceeding 0.50 mm, and more preferably 0.60 mm or more.

[0081] When the thickness of the AGM separator is 0.50 mm or less, the total amount of electrolyte that can be retained by the AGM separator decreases, thereby reducing the function of preventing the electrolyte from stratifying. In addition, the absolute strength of the AGM separator decreases.

[0082] On the other hand, the thickness of the AGM separator is preferably less than 1.80 mm, more preferably 1.70 mm or less, and further preferably 1.65 mm or less.

[0083] When the thickness of the AGM separator is 1.80 mm or more, the interval between the electrode plates of the lead-acid battery becomes wider, and the battery characteristics deteriorate.

[0084] In the separator for lead acid battery (AGM separator) of the present invention, the tensile strength (sheet strength) of the AGM separator is preferably 0.2 N / mm 2 The mechanical strength is more preferably 0.7N / mm 2 above.

[0085] If the tensile strength (sheet strength) is less than 0.2N / mm 2 , the assembly performance of the lead-acid battery and the basic physical properties during charge and discharge reactions are reduced, and the battery life is shortened.

[0086] In the lead acid battery separator (AGM separator) of the present invention, the puncture strength of the AGM separator preferably has a mechanical strength of 6 N / mm or more, more preferably 8 N / mm or more, and even more preferably 10 N / mm or more in order to improve the assemblability of the lead acid battery.

[0087] If the puncture strength is less than 6 N / mm, the assembly performance of the lead-acid battery and the basic physical properties during charge and discharge reactions are deteriorated, and the battery life is shortened.

[0088] In the lead-acid battery separator (AGM separator) of the present invention, it is necessary to prevent peeling from occurring at the bag processing portion (sealing portion) of the bag processing by ultrasonic sealing after the cycle life test. Therefore, when the above-mentioned separator after the bag processing by ultrasonic sealing is boiled in water for 60 minutes, the peel strength at the sealing portion (fusion portion) of the above-mentioned separator is preferably 1N / 20mm or more, and more preferably 2N / 20mm or more.

[0089] In separators having a peel strength of 1 N / 20 mm or more at the sealed portion (fused portion) of the separator when boiled in water for 60 minutes, no peeling occurred in the bag processing portion (sealed portion) sealed by ultrasonic wave after the cycle life test.

[0090] As for the cycle life test, it is a test carried out in a state of overcharging, and it is considered to be a condition equivalent to boiling for 60 minutes. In addition, it is known that: as for the electrolyte used for lead-acid batteries, sulfuric acid aqueous solution is usually used, but the boiling test using sulfuric acid aqueous solution has a safety problem, and can be replaced by boiling with water.

[0091] In the lead acid battery separator (AGM separator) of the present invention, the liquid absorption height of the AGM separator is preferably 20 mm / min or more, more preferably 25 mm / min or more, in order to retain the electrolyte and maintain the capacity.

[0092] If the liquid absorption height is less than 20 mm / min, the electrolyte retention in the lead-acid battery is reduced, and the capacity is reduced.

[0093] In the separator for lead acid battery (AGM separator) of the present invention, the wettability of the AGM separator is preferably 100 seconds / 3 ml or less, more preferably 60 seconds / 3 ml or less, in order to improve the injection speed of the electrolyte.

[0094] If the wettability exceeds 100 seconds / 3 ml, the production speed of the lead acid battery decreases.

[0095] In the separator for lead acid battery (AGM separator) of the present invention, the water absorption of the AGM separator is preferably 4 g / g or more, more preferably 5 g / g or more, in order to maintain the capacity of the lead acid battery.

[0096] If the water absorption is less than 4 g / g, the capacity of the lead acid battery decreases.

[0097] In the separator for lead acid battery (AGM separator) of the present invention, the maximum pore diameter of the AGM separator is preferably less than 100 μm, more preferably 40 μm or less, from the viewpoint of preventing stratification of the electrolyte.

[0098] In the separator for lead acid battery (AGM separator) of the present invention, the elongation of the AGM separator is preferably in the range of 2.0% to less than 20.0%, more preferably in the range of 2.5% to 15.0%.

[0099] During the charge and discharge reaction when the battery is used, the AGM separator expands and contracts due to repeated absorption and release of the electrolyte.

[0100] In addition, the AGM spacer is mainly shipped in a roll form, and the AGM spacer is pulled out from the roll for use when assembling the lead-acid battery. Therefore, when the elongation of the AGM spacer measured at room temperature is 20.0% or more, the AGM spacer is stretched due to the force when the AGM spacer is pulled out, and the dimensions of the AGM spacer in the width direction and the thickness direction change.

[0101] In such a case, the distance between the electrodes and their dimensions set to prevent the side short circuit of the lead-acid battery electrodes change, which may cause the battery to short-circuit early.

[0102] Furthermore, when the AGM separator is pulled out from the roll for use during the assembly of the lead-acid battery, if the elongation is less than 2.0%, cracks may occur in the AGM separator, resulting in a defective product that cannot be shipped.

[0103] Among the heat-bondable organic fibers having a core-sheath structure preferably used in the lead-acid battery separator (AGM separator) of the present invention, those capable of ultrasonic sealing include PET / PET, PET / PE, and the like.

[0104] PET / Co-PET using copolymerized PET (Co-PET) having a low glass transition temperature (about 70°C) in the sheath portion, has high adhesion between organic fibers during drying in the production process of the AGM spacer, and has excellent tensile strength and puncture strength. In addition, PET has an ester bond, so it is an AGM spacer with good wettability to the electrolyte.

[0105] However, if it is only PET / PET fibers, when exposed to the electrolyte for a long time in the lead-acid battery, the wettability is good, so the sealing part of the bagged AGM separator swells, the adhesion between the fibers is easily removed, and there is also a disadvantage that the peel strength (sealing strength) of the AGM separator is reduced.

[0106] On the other hand, PET / PE fiber uses PE in the sheath part. Since PE has no ester bond, the wettability of the AGM separator is low. Even if it is exposed to the electrolyte for a long time in the lead-acid battery, the peel strength (sealing strength) of the AGM separator is unlikely to decrease.

[0107] In addition, as an ultrasonically sealable spacer, there is an AGM spacer using PE paste-like heat-fusible fibers, and although the peel strength (sealing strength) of the AGM spacer is unlikely to decrease, it has the disadvantage of low tensile strength and puncture strength. It is presumed that this is because the PE paste-like heat-fusible fibers are non-uniformly melted on the surface of the AGM spacer during the production of the AGM spacer, so the tensile strength and puncture strength are reduced.

[0108] Therefore, in the present invention, when using a single type of heat-fusible organic fiber with a core-sheath structure, the heat-fusible organic fiber with a core-sheath structure in which the sheath portion is composed of a crystalline polyolefin resin and the core portion is composed of a polyester resin (for example, PET / crystalline PE) is the preferred heat-fusible organic fiber with a core-sheath structure, and its blending amount is preferably greater than 15 weight % and less than 40 weight %.

[0109] Moreover, in order to obtain excellent puncture strength, a heat-fusible organic fiber with a core-sheath structure in which the sheath is composed of an amorphous polyester resin and the core is composed of a crystalline polyester resin (for example, PET / amorphous Co-PET) can also be used as a single type of heat-fusible organic fiber with a core-sheath structure, and its blending amount is preferably greater than 20 weight % and less than 40 weight %.

[0110] In addition, when two types of heat-fusible organic fibers having a core-sheath structure are used, a preferred combination of heat-fusible organic fibers having a core-sheath structure includes a heat-fusible organic fiber having a core-sheath structure in which the sheath portion is composed of a crystalline polyolefin resin and the core portion is composed of a polyester resin (for example, PET / crystalline PE), a heat-fusible organic fiber having a core-sheath structure in which the sheath portion is composed of a crystalline polyester resin and the core portion is composed of a crystalline polyester resin (for example, PET / crystalline Co-PET), or a heat-fusible organic fiber having a core-sheath structure in which the sheath portion is composed of an amorphous polyester resin and the core portion is composed of a crystalline polyester resin (for example, PET / amorphous Co-PET). Moreover, with respect to their respective compounding amounts, the thermally fusible organic fiber having a core-sheath structure in which the sheath portion is composed of a crystalline polyolefin resin and the core portion is composed of a polyester resin (e.g., PET / crystalline PE) is greater than 10 weight % and less than 40 weight %, and the thermally fusible organic fiber having a core-sheath structure in which the sheath portion is composed of a crystalline polyester resin and the core portion is composed of a crystalline polyester resin (e.g., PET / crystalline Co-PET), or the thermally fusible organic fiber having a core-sheath structure in which the sheath portion is composed of an amorphous polyester resin and the core portion is composed of a crystalline polyester resin (e.g., PET / amorphous Co-PET) is preferably greater than 0 weight % and less than 30 weight %.

[0111] When two types of heat-fusible organic fibers having a core-sheath structure are used in the present invention, heat-fusible organic fibers having a core-sheath structure whose sheath portion is composed of amorphous heat-fusible organic fibers (for example, amorphous Co-PET) having a glass transition temperature at 40°C to 100°C are mixed and used, and the lead-acid battery separator (AGM separator) produced in this way can be observed by thermal analysis using a differential scanning calorimeter (DSC) at 40°C to 100°C. The glass transition temperature of the amorphous heat-fusible organic fibers used can be observed. In addition, when a heat-fusible organic fiber with a core-sheath structure whose sheath portion is composed of a crystalline polyolefin resin (e.g., crystalline PE) is mixed and used, the melting point of the heat-fusible organic fiber used can be observed at a temperature above 100°C and below 200°C by thermal analysis using a differential scanning calorimeter (DSC). When a heat-fusible organic fiber with a core-sheath structure whose sheath portion is composed of a crystalline polyester resin (e.g., crystalline Co-PET) is mixed and used, the melting point of the heat-fusible organic fiber used can be observed at a temperature above 100°C and below 200°C by thermal analysis using a differential scanning calorimeter (DSC). Similarly, when a heat-fusible organic fiber having a core-sheath structure whose core is composed of a crystalline polyester resin (e.g., PET) is mixed and used, the melting point of the heat-fusible organic fiber used can be observed at a temperature above 200°C and below 300°C by thermal analysis using a differential scanning calorimeter (DSC).

[0112] Example

[0113] Hereinafter, the present invention will be described in more detail with reference to Examples, Conventional Examples, and Comparative Examples, but the present invention is not limited to the following Examples unless the scope of the invention exceeds the scope of the invention.

[0114] Lead acid battery separators (AGM separators) of Examples 1 to 11, Conventional Examples 1 to 2, and Comparative Examples 1 to 15 were produced using the following raw materials.

[0115] [Materials]

[0116] (1) Micro glass fiber

[0117] A: CMLF-307R manufactured by Nippon Sheet Glass Co., Ltd., number average fiber diameter 0.7 μm

[0118] B: CMLF-114R manufactured by Nippon Sheet Glass Co., Ltd., number average fiber diameter 4 μm

[0119] (2) Thermally fusible organic fibers

[0120] A: Teijin Ltd. Tepilus TJ04EN, 2-component core-sheath type (core: polyethylene terephthalate, sheath: crystalline polyethylene), fineness 1.2 dtex

[0121] B: Meltie 4080 manufactured by Unichika Co., Ltd., 2-component core-sheath type (core: polyethylene terephthalate, sheath: amorphous copolymer polyethylene terephthalate), fineness 1.7 dtex

[0122] C: Teijin Ltd. Tepilus TJ04CN, 2-component core-sheath type (core: polyethylene terephthalate, sheath: amorphous copolymer polyethylene terephthalate), fineness 1.1 dtex

[0123] D: Ube Eco-Smo Co., Ltd., SIMTECH SCE, 2-component core-sheath type (core: polypropylene, sheath: crystalline polyethylene), fineness 1.7 dtex

[0124] E: Cabbeen 7080 manufactured by Unichika Co., Ltd., 2-component core-sheath type (core: polyethylene terephthalate, sheath: crystalline copolymer polyethylene terephthalate), fineness 1.1 dtex

[0125] F: Melt 4000 manufactured by Yunichika Co., Ltd., 1-component full-melt type (amorphous copolymerized polyethylene terephthalate), fineness 2.2 dtex

[0126] G: SWP EST-2 (synthetic polyethylene pulp) manufactured by Mitsui Chemicals, Inc., fiber diameter 2 to 30 μm

[0127] (3) Non-adhesive monofilament organic fibers

[0128] EP133 (polyethylene terephthalate) manufactured by Kurara Co., Ltd., fineness 1.45dtex

[0129] (4) Inorganic fillers

[0130] Silica: BG-3 made by Edotron AG

[0131] Diatomaceous earth: Diatomaceous earth: Radiolate F manufactured by Showa Chemical Industry Co., Ltd.

[0132] [Manufacturing of AGM spacers]

[0133] According to the formulations shown in Tables 1 and 2, separators for lead acid batteries (AGM separators) of Examples 1 to 11, Conventional Examples 1 to 2, and Comparative Examples 1 to 15 were produced by the following procedures.

[0134] About 7 to 13 g of the raw material is placed in a container of a commercial mixer (MX-152SP manufactured by Panasonic), and about 1000 ml of water is added, and the mixture is dissociated for 60 seconds (rotation speed: about 9700 rpm). The slurry sample solution is placed in a square sheet machine for the experiment, and water is further added. After uniform stirring to a concentration of 0.25% by weight, the mixture is made into sheets. The mixture is dried at a temperature of 100°C for 30 minutes in a box dryer, and then heated and dried at 180°C for 3 minutes to produce an AGM spacer. When drying the sheets, be careful not to fill the dryer with water vapor.

[0135] [Test and evaluation methods]

[0136] The above-mentioned Examples, Conventional Examples and Comparative Examples were evaluated under the following conditions, and the results are summarized in Tables 1 and 2.

[0137] (1) Thickness (mm)

[0138] The prepared AGM separators were cut into pieces of 100 mm x 100 mm as test pieces, 10 of which were stacked and measured according to the method described in 7.2.2.b) of the Battery Industry Association Standard SBA S 0406-2017 Edition for AGM separators for lead-acid batteries.

[0139] In the measurement, a load of 196 N was quietly applied uniformly to the entire surface of 10 stacked test pieces, and the thickness of the four corners of the AGM separator was measured, and the average value was expressed.

[0140] (2) Density (g / cm 3 )

[0141] The value was measured according to the method described in Section 7.2.3 of the Battery Industry Association Standard SBA S 0406-2017 for AGM separators for lead-acid batteries, and calculated by the following formula.

[0142] Apparent density (g / cm 3 )=[weight(g / m 2 )]÷[Thickness (mm)]÷1000

[0143] (3) Tensile strength (N / mm) 2 )

[0144] The following procedure was followed based on the method described in Item 7.2.7 of the Battery Industry Association Standard SBA S 0406-2017 for AGM separators for lead-acid batteries.

[0145] The prepared AGM spacer is cut into a size of 10 mm × 70 mm to prepare a test piece. A Schöpper-type tensile tester or equivalent thereof with a tensile strength of 294 N or less is used. The chuck (clamp) interval is set to 50 mm. The test piece is stretched at a speed of 200 mm per minute, and the maximum value until the test piece breaks is measured.

[0146] (4) Puncture strength (N / mm)

[0147] The manufactured AGM spacer cut into a size of 20 mm x 150 mm is clamped in a fixing fixture with a hole of 5 mm in diameter, and a hemispherical iron rod with a top end of 2 mm in diameter (r = 1 mm) is pierced from the top at a speed of 50 mm / min. The maximum load (N) until the test piece is pierced is measured and divided by the thickness (mm) of the AGM spacer to calculate the puncture strength.

[0148] (5) Can ultrasonic sealing bags be processed?

[0149] Using an ultrasonic welder SONOPET JII manufactured by Seidensha Electronics Co., Ltd., the AGM spacer was cut into a size of 110 mm × 260 mm under the conditions of welding energy 300 J, holding time 1 s, and sealing line width 2 mm, folded in half with the longitudinal direction as the center, and both ends were placed in the ultrasonic welder. The case where the ultrasonic welder could be sealed was marked as "○", and the case where the sealing could not be performed was marked as "×".

[0150] (6) Peel strength (after ultrasonic sealing (before boiling treatment), N / 20mm)

[0151] The prepared AGM separator was ultrasonically sealed by the method (5) above, and then cut into pieces with a width of 20 mm so that the sealed portion was inserted. The sealed portion was stretched at 50 mm / min using a tensile tester, and the maximum load (N) until peeling occurred was measured as the peel strength after ultrasonic sealing (before boiling treatment).

[0152] The case where ultrasonic sealing could not be performed by the above method (5) was marked as "×".

[0153] (7) Peel strength (after ultrasonic sealing (after boiling treatment), N / 20mm)

[0154] The sample cut into 20 mm width after ultrasonic sealing in the same manner as in (6) above was placed in a beaker containing 500 ml of water and heated with a mantle heater to boil for 60 minutes. The boiled sample was taken out of the beaker and naturally cooled to room temperature. The maximum load (N) until peeling occurred was measured under the same conditions as in (6) above, and this was taken as the peel strength after boiling treatment.

[0155] The case where ultrasonic sealing could not be achieved by the method (5) above or the case where the seal portion peeled off before mounting on the tensile tester was marked as "×".

[0156] (8) Maximum pore diameter (μm)

[0157] The test piece was immersed in ethanol solution, and then the ethanol solution was injected into the test piece at a height of 10 mm, and pressurized air was flowed in from the bottom (AGM spacer surface). The ventilation pressure was gradually increased, and the pressure value when bubbles (bubbles) were first generated through the test piece was read by a pressure gauge (mm), and the maximum pore diameter was calculated by the following calculation formula.

[0158] At this time, the temperature of the ethanol liquid was measured, and the surface tension at that temperature was substituted into the calculation formula.

[0159] Maximum pore diameter (μm) = [4 × (surface tension of liquid) × 104] ÷ [980 × {(pressure gauge reading, mm) - (height of liquid on the sample, 10 mm)}]

[0160] (9) Liquid absorption height (mm / min)

[0161] The AGM spacer produced was cut into a size of 15 mm in width and 10 cm in height as a sample. The sample was suspended in a vertical state, and 1 cm from the lower end was immersed in a sulfuric acid aqueous solution with a specific gravity of 1.30. The height (mm) at which the sulfuric acid aqueous solution was absorbed for 1 minute was measured and defined as the liquid absorption height.

[0162] (10) Wettability (seconds / 3ml)

[0163] The AGM spacer was cut into a size of 100 mm x 100 mm as a sample. 3 ml of a colored aqueous sulfuric acid solution (red) with a specific gravity of 1.30 placed in a burette was dripped into the sample at a rate of 2.2 ml / sec, and the time until the sample completely penetrated was measured as wettability.

[0164] (11) Water absorption (g / g)

[0165] The AGM spacer produced was cut into a product of 100 mm × 100 mm size as a sample. After measuring the weight of the sample (W1, g), it was immersed in a bucket filled with water for 1 minute. The immersed sample was taken out and placed on a table with a 45-degree inclination. After standing for 30 seconds, the weight of the sample in a state including water was measured (W2, g). The water absorption was calculated by the following formula.

[0166] Water absorption (g / g) = (W2-W1) / W1

[0167] (12) Thermal analysis using differential scanning calorimeter (DSC)

[0168] The produced AGM separator was subjected to differential scanning calorimetry analysis (measurement temperature range: 40°C to 350°C, heating rate: 10°C / min) using a differential scanning calorimeter (DSC) (DSC60 manufactured by Shimadzu Corporation) in a nitrogen atmosphere (flow rate: 100 ml / min).

[0169] The glass transition temperature (°C) and melting point (°C) were determined from the obtained DSC curve.

[0170] (13) Opening holes during lead-acid battery assembly

[0171] Using the manufactured AGM separator, a lead-acid battery of 55D23L specification was manufactured based on JISD5301:2019.

[0172] The lead-acid battery produced before the electrolyte solution was injected was disassembled, and visual inspection was performed to check whether or not a hole was formed in the AGM separator.

[0173] The case where no opening occurred was recorded as “no opening (○)”, and the case where an opening occurred at least at one place was recorded as “an opening (×)”.

[0174] The AGM separators of Comparative Examples 14 and 15 did not contain micro glass fibers and therefore did not have an electrolyte retention function. Therefore, the tests performed after the lead acid battery was assembled were omitted.

[0175] (14) Presence of peeling after cycle life test

[0176] Lead-acid batteries were manufactured using the AGM separators. Cycle life tests (200 cycles) were performed in accordance with JIS C8702-1:2009 "Small valve-controlled lead-acid batteries Part 1: General requirements, functional characteristics and test methods". The lead-acid batteries after the test were disassembled and visually checked to see if peeling occurred in the bag processing part (sealing part) of the AGM separator.

[0177] The case where no peeling occurred was recorded as “no peeling (○)”, and the case where peeling occurred although it was slight was recorded as “peeling occurred (×)”.

[0178] The AGM separators of Comparative Examples 14 and 15 did not contain micro glass fibers and therefore did not have an electrolyte retention function. Therefore, the tests performed after the lead acid battery was assembled were omitted.

[0179] The evaluation results of Examples 1 to 11, Conventional Examples 1 to 2, and Comparative Examples 1 to 15 are summarized in Tables 1 and 2.

[0180]

[0181]

[0182] From the test results of Examples 1 to 11, Conventional Examples 1 to 2, and Comparative Examples 1 to 15 shown in Tables 1 to 2, it can be seen that, for the lead-acid battery separator (AGM separator) whose peel strength at the sealed portion (fused portion) of the lead-acid battery separator (AGM separator) is 1N / 20mm or more when the AGM separator after bagging by ultrasonic sealing is boiled in water for 60 minutes, peeling of the bagging portion (sealing portion) does not occur when the cycle life test is performed. In addition, it can be seen that, for the lead-acid battery separator (AGM separator) whose puncture strength is 6N / mm or more, the lead-acid battery separator (AGM separator) does not have an unfavorable situation such as a hole being opened when the lead-acid battery is assembled. In addition, in the lead-acid battery separators (AGM separators) of Examples 5 to 11, the glass transition temperature of the heat-fusible organic fiber having a core-sheath structure composed of amorphous heat-fusible organic fiber (amorphous Co-PET) used in the sheath portion can be observed at about 70° C. by thermal analysis using a differential scanning calorimeter (DSC). The lead-acid battery separators (AGM separators) of Examples 5 to 11 using the heat-fusible organic fiber having a core-sheath structure composed of amorphous Co-PET having a glass transition temperature of about 70° C. have a puncture strength of 15.1 N / mm or more.

[0183] On the other hand, in the prior art examples 1 and 2 which do not contain organic fibers having a core-sheath structure as heat-fusible organic fibers, when the lead-acid battery separator (AGM separator) after bag processing using ultrasonic sealing was boiled in water for 60 minutes, the peel strength at the sealed portion (fused portion) of the lead-acid battery separator (AGM separator) was 1N / 20mm or more. However, since the puncture strength was less than 6N / mm, the lead-acid battery separator (AGM separator) had an unfavorable situation such as a hole being opened when the lead-acid battery was assembled, and it was found that the lead-acid battery separator (AGM separator) had a problem in strength.

[0184] The test results of Examples 1 to 11, Previous Examples 1 to 2 and Comparative Examples 1 to 15 confirm that the lead-acid battery separator (AGM separator) of the present invention has the high strength and high electrolyte retention function required for lead-acid battery separators in recent years, and can provide a lead-acid battery separator (AGM separator) in which no peeling of the bag processing part (sealing part) occurs during a cycle life test.

[0185] Industrial Applicability

[0186] The lead-acid battery separator (AGM separator) of the present invention has the high strength and high electrolyte retention function required of lead-acid battery separators in recent years, and does not peel off the bag processing part (sealing part) during the cycle life test, so it can improve the production rhythm in lead-acid battery manufacturing.

Claims

1. A separator for a lead-acid battery, which is mainly composed of micro glass fibers and heat-fusible organic fibers, wherein: When the separator after bagging is boiled in water for 60 minutes, the peel strength at the sealing portion (fusion bonded portion) of the separator is 1 N / 20 mm or more.

2. The lead acid battery separator according to claim 1, wherein The bag processing is performed by ultrasonic sealing.

3. The separator for a lead acid battery according to claim 1, wherein The thickness of the separator when pressurized to 20 kPa is greater than 0.50 mm and less than 1.80 mm.

4. The separator for a lead acid battery according to claim 1, wherein The puncture strength of the spacer is 6 N / mm or more.

5. The separator for a lead acid battery according to claim 1, wherein The wettability of the spacer is 100 seconds / 3 ml or less.

6. The separator for a lead acid battery according to claim 1, wherein The tensile strength of the spacer is 0.2 N / mm 2 above.

7. The separator for a lead acid battery according to claim 1, wherein The heat-fusible organic fiber is an organic fiber having a core-sheath structure, wherein the sheath portion is made of a crystalline heat-fusible polyolefin resin or a crystalline heat-fusible polyester resin.

8. The lead acid battery separator according to claim 1, wherein The heat-fusible organic fiber is an organic fiber having a core-sheath structure, and the sheath portion is an amorphous heat-fusible polyester resin.

9. The separator for a lead acid battery according to claim 8, characterized in that In thermal analysis of the lead acid battery separator using a differential scanning calorimeter (DSC), the glass transition temperature of the organic fiber derived from the core-sheath structure of the thermally fusible polyester resin having an amorphous sheath portion was observed at 40°C to 100°C.

10. The separator for a lead acid battery according to claim 1, wherein The thermally fusible organic fiber has a fineness of 0.4 dtex or more and 2.5 dtex or less.

11. The separator for a lead acid battery according to claim 1, wherein The blending amount of the thermally fusible organic fiber is 10% by weight or more.

12. The separator for a lead acid battery according to claim 1, wherein The number average fiber diameter of the micro glass fibers is 4.5 μm or less.

13. The separator for a lead acid battery according to claim 1, wherein The total amount of the micro glass fibers and the thermally fusible organic fibers blended is 60% by weight or more. 14 . A lead acid battery using the separator for a lead acid battery according to claim 1 .

Citation Information

Patent Citations

  • Mat for bag type separator

    JP1982098975A

  • Rubber composition

    JP1990034644A

  • Magnetic tape device

    JP1990141955A

  • Bag-shape separator for lead-acid battery

    JP1994176749A

  • Sealed lead-acid battery

    JP1997017406A